Performance characteristics of buildings in the assessment of revitalization Leeds = Właściwości użytkowe budynków w ocenie potrzeb rewitalizacji - Nowogońska, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Performance characteristics are an indicator of both, the technical as well as aesthetic state of buildings. Aesthetic needs are in disagreement with the merciless aging process. The beauty of a city is formed not only by the original forms of new residential buildings, but also by existing tenement housing; thus preserving their aesthetics becomes a necessity.
Keywords: residential buildings; building diagnostics; revitalization; determination of renevation needs; budynki mieszkalne; diagnostyka budynku; rewitalizacja; potrzeby rewitalizacji